2012
DOI: 10.1186/1748-717x-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cell survival after irradiation via clonogenic assay versus multiple MTT Assay - A comparative study

Abstract: For studying proliferation and determination of survival of cancer cells after irradiation, the multiple MTT assay, based on the reduction of a yellow water soluble tetrazolium salt to a purple water insoluble formazan dye by living cells was modified from a single-point towards a proliferation assay. This assay can be performed with a large number of samples in short time using multi-well-plates, assays can be performed semi-automatically with a microplate reader. Survival, the calculated parameter in this as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(184 citation statements)
references
References 10 publications
6
176
0
2
Order By: Relevance
“…the MTT assay) in comparison to colony forming. It has previously been shown that tetrazolium--based assays to some degree overestimate the surviving fraction for absorbed doses over approximately 8−10 Gy (27). But since we limited this study to maximum 10 Gy and also used the WST--1 assay for all our evaluations, we believe that the comparison of the effects of gamma and alpha--particle irradiations are comparable.…”
Section: Radiation Sensitivity Measurementsmentioning
confidence: 94%
“…the MTT assay) in comparison to colony forming. It has previously been shown that tetrazolium--based assays to some degree overestimate the surviving fraction for absorbed doses over approximately 8−10 Gy (27). But since we limited this study to maximum 10 Gy and also used the WST--1 assay for all our evaluations, we believe that the comparison of the effects of gamma and alpha--particle irradiations are comparable.…”
Section: Radiation Sensitivity Measurementsmentioning
confidence: 94%
“…The total number of colonies containing >50 cells were counted using a binocular light microscope (Olympus Corporation, Tokyo, Japan). Following the counting of the colonies, the plating efficiency (PE) and survival fraction (SF) were calculated using the following equations (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple-MTS assay was used to estimate the survival fraction (17). In multiple-MTS assay, the cell growth data (the number of viable cells) are collected daily to draw the cell growth curve.…”
Section: Survival Fraction-based Multiple-mts Assaymentioning
confidence: 99%